Evaluation of customer satisfaction level: a study on customer service in general banking Prime Bank-Pragati Sarani Branch - Rashid, Kamrun Nahar (Brac University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters of Business Administration, 2019.